Effect of wheat germination on nutritional properties and the flavor of soy sauce. (August 2022) - Shi, Huiqin; Li, Jingjing; Zhang, Yujie; Ding, Kaili; Zhao, Guozhong; Duan, Xiang; Hadiatullah, Hadiatullah
Abstract: Germination pretreatment of raw materials is an effective technique to improve the flavor and nutritional value of soy sauce. In this study, we aimed to investigate the effects of germinated wheat (GW-24h, GW-48h, and GW-72h) and un-germinated wheat (raw and fried wheat) on nutritional properties, flavor profiles, and microbial structure of soy sauce. The results showed that, the content of amino acid nitrogen, total nitrogen, reducing sugars, isoflavones, and γ-Aminobutyric acid (GABA) after germination was 15.4%, 9.4%, 176.7%, 41.4%, and 238.0%, respectively, which were higher than that of un-germinated wheat. In addition, germinated wheat revealed a beneficial effect on antioxidant activity. Un-germinated wheat (e.g., fried wheat) has a richer flavor profile but carries the risk of contaminants (e.g., acetamide). In contrast, the germinated group has higher contents of acetoin, which contributes to desirable flavor and is a precursor to bioactive compounds of soy sauce. According to the microbial diversity, germinated wheat reduced bacterial diversity, which was favourable for soy sauce fermentation. Overall, this study approves that germinated wheat can effectively improve biological properties and flavor profile of soy sauce, providing new technical insight to improve soy sauce products. Graphical abstract: Image 1 Highlights: Germinated wheat was used as the raw material for soy sauce fermentation. Germinated wheat promoted the nutritional properties of soy sauce. Germinated wheat increased the flavor substances of soy sauce. Bacillus inhibited the pathogenic food-borne Stenotrophomonas .